A de novo mutation of the SOX10 gene associated with inner ear malformation in a Guangxi family with Waardenburg syndrome type II. (June 2021) - Niu, Zhijie; Lai, Yongjing; Tan, Songhua; Tang, Fen; Tang, Xianglong; Su, Yupei; Liu, Lei; Xie, Lihong; Fang, Qin; Xie, Mao; Tang, Anzhou
Abstract: Objective: Waardenburg syndrome type 2 (WS2) is a rare neural-crest disorder, characterized by heterochromic irides or blue eyes and sensorineural hearing loss. The aim of this study was to analyze the clinical features and investigate the genetic cause of WS2 in a small family from Guangxi Zhuang Autonomous region. Methods: Whole-exome sequencing and mutational analysis were used to identify disease-causing genes in this family. Results: A de novo missense mutation, C.355C > T (p. Arg119Cys), in exon 2 of SOX10 was related to inner ear malformation in the proband and identified by whole exon sequencing, but this mutation was absent in normal controls and any public databases. According to nucleic acid sequence and protein bioinformatic analysis, this mutation is considered the cause of WS2 without neurologic involvement in the proband. Conclusions: Our findings provide an accurate genetic diagnosis, counseling, and rehabilitation for family members and may contribute to further genotype-phenotype correlation studies of the SOX10 gene.